Human gamma-satellite DNA maintains open chromatin structure and protects a transgene from epigenetic silencing - Kim, Jung-Hyun; Ebersole, Thomas; Kouprina, Natalay; Noskov, Vladimir N.; Ohzeki, Jun-Ichirou; Masumoto, Hiroshi; Mravinac, Brankica; Sullivan, Beth A.; Pavlicek, Adam; Dovat, Sinisa; Pack, Svetlana D.; Kwon, Yoo-Wook; et al. (Genome Research, 2009)
The role of repetitive DNA sequences in pericentromeric regions with respect to kinetochore/heterochromatin structure and function is poorly understood. Here, we use a mouse erythroleukemia cell (MEL) system for studying how repetitive DNA assumes or is assembled into different chromatin structures. We show that human gamma-satellite DNA arrays allow a transcriptionally permissive chromatin conformation in an adjacent transgene and efficiently protect it from epigenetic silencing. These arrays contain CTCF and Ikaros binding sites. In MEL cells, this gamma-satellite DNA activity depends on binding of Ikaros proteins involved in differentiation along the hematopoietic pathway. Given our discovery of gamma-satellite DNA in pericentromeric regions of most human chromosomes and a dynamic chromatin state of gamma-satellite arrays in their natural location, we suggest that gamma-satellite DNA represents a unique region of the functional centromere with a possible role in preventing heterochromatin spreading beyond the pericentromeric region.
10.1101/gr.086496.108